Integrated learning: ways of fostering the applicability of teachers’ pedagogical and psychological knowledge - Harr, Nora; Eichler, Andreas; Renkl, Alexander (Frontiers in Psychology, 2015)
In teacher education, general pedagogical and psychological knowledge is often taught separately from the teaching subject itself, potentially leading to inert knowledge. In an experimental study with 69 mathematics student teachers, we tested the benefits of fostering the integration of pedagogical content knowledge and general pedagogical and psychological knowledge with respect to knowledge application. Integration was fostered either by integrating the contents or by prompting the learners to integrate separately-taught knowledge. Fostering integration, as compared to a separate presentation without integration help, led to more applicable pedagogical and psychological knowledge and greater simultaneous application of pedagogical and psychological knowledge and pedagogical content knowledge. The advantages of fostering knowledge integration were not moderated by the student teachers’ prior knowledge or working memory capacity. A disadvantage of integrating different knowledge types referred to increased learning times.